Auditoria en Seguridad Vial, Ruta 50RS01 Apia – la Virginia, PR 10+000 al PR 16+000, Conexión Troncal de Occidente – Transversal las Animas - Bogotá (2023)
The central purpose of this study was to carry out a Road Safety Audit of certain components that make up the road infrastructure, in order to evaluate their status in relation to users who transit through the section that extends from PR 10 to PR 16, on the route between Apia and Virginia Risaralda. In order to achieve this goal, an exhaustive analysis of the current state of knowledge in the field was carried out, a theoretical framework was developed, a methodology of a quantitative and descriptive nature, and multiple field trips were carried out to achieve the established objectives.